2022
DOI: 10.1155/2022/4241049
|View full text |Cite
|
Sign up to set email alerts
|

Swarm Intelligence Algorithms for Portfolio Optimization Problems: Overview and Recent Advances

Abstract: Due to the volatility and uncertainty of the financial market, investors often use the form of portfolio to actively manage their assets. Portfolio optimization (PO) is becoming more and more important for investors. However, PO is frequently a kind of NP-hard problem in the field of modern financial optimization, which has gradually attracted the attention and interest of researchers. Some efficient mathematical models were built to describe the return and risk of portfolio. A lot of precise and approximate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…In general, two objectives can be chosen for the portfolio optimization problem. The portfolio optimization problem can be defined as an effort to arrange financial assets (stock, bond, gold, and so on) to maximize the return or control the risk [36].…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…In general, two objectives can be chosen for the portfolio optimization problem. The portfolio optimization problem can be defined as an effort to arrange financial assets (stock, bond, gold, and so on) to maximize the return or control the risk [36].…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…Transitioning to portfolio optimization methodologies, incorporating three distinct methodologies-naive portfolio construction, Sharpe ratio maximization, and kurtosis minimization-offers a comprehensive approach that considers various aspects of risk and return (Hanif et al 2023). Naive portfolio construction involves equally weighting the assets in a portfolio and serves as a straightforward baseline strategy (Chen et al 2022). Conversely, Sharpe ratio maximization aims to enhance the risk-adjusted return of a portfolio, effectively balancing risk and return (Dabbous et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Portfolios of the available choices are important. By generalizing the research of Markowitz [9], Chen and colleagues [12], used swarm intelligence algorithms to address portfolio optimization. Their swarm intelligence algorithm was mainly inspired and developed by observing swarms in nature, and included self-organization, self-adaptation, and self-learning from biological populations (e.g., birds, elephants, wolves).…”
Section: Of 24mentioning
confidence: 99%
“…Their research [12] showed that swarm intelligence algorithms can be efficient and can produce satisfactory solutions in solving portfolio optimization (PO) problems. However, from [12], ) "how to achieve the maximum benefit and minimum risk of dynamic multi-period portfolio is a worthy study problem in the future. .…”
Section: Of 24mentioning
confidence: 99%
See 1 more Smart Citation